ANALYSIS OF FEATURES OF ANALOG-TO-DIGITAL CONVERSION "DURATION-CODE" - MARTYNIUK, Tatiana; KOZHEMIAKO, Andryi; BORTNYK, Gennadiy; VOINALOVYCH, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents the analysis results of the features of the analog-to-digital conversion of a continuous value as the duration of the input signal into the output digital code. Converters that work according to this principle are known as analog-code converters, and the conversion principle is a type of well-known pulse-width modulation (PWM). Information of a different nature can be used as input analog information, for example, the duration of an optical, electrical or sound signal. Specifically, the principle of this conversion with further processing of digital information uses a well-known logic-time basis, since the main operational parameter of the conversion is the duration of time, and the processing of digital data is performed according to the rules of picture logic with natural parallelism of processing on a two-dimensional field of information presentation. A feature of this approach to the conversion of input signals duration is the coding of output digital information in unit codes. In this case, two well-known unit codes are involved: unit normal and unit positional codes. This is because unit encoding is best suited for duration-to-code analog-to-digital conversion due to the quantization of the input signal duration by the trigger time of a line bistable elements. It is shown that the most acceptable implementation in terms of speed and energy consumption is the symbiosis of these two codes, since the unit normal code is faster when recording information, but loses to the unit positional code in terms of energy consumption when storing data. Taking into account the controllability of a unit positional code, the area of its effective application is the coding of the states of control devices and the addressing of the contents of storage devices, for example, as part of associative processors.